Christian Divination in Late Antiquity - Wiśniewski, Robert, 1968- (Social worlds of late antiquity and the early Middle Ages., 2020)
In Late Antiquity, people commonly sought to acquire hidden knowledge about the past, the present, and the future, using a variety of methods. While Christians acknowledged that these methods could work effectively, in theory they were not allowed to make use of them. In practice, they behaved in diverse ways. Some probably renounced any hope of learning about the future. Others resorted to old practices regardless of the consequences. A third option was to construct divinatory methods that were effective yet religiously tolerable. This book is devoted to the study of such practices and their practitioners, and provides answers to essential questions concerning Christian divination. How did it develop? How closely were Christian methods related to older, traditional practices? Who used them and in which situations? Who offered oracular services? And how were they perceived by clerics, intellectuals, and common people?